A social psychology of protest individuals in action - Stekelenburg, Jacquelien van; Klandermans, Bert (Cambridge University Press, 2024)
Over the last few decades, we have witnessed increasing incidents of collective action. Collective action is a matter of demand by citizens who are aggrieved, supply by protest organizations/individuals, and mobilization through effective communication networks. This volume elaborates on the processes and mechanisms responsible for these dynamics"-- Provided by publisher.